Endophilin2 Interacts with GluA1 to Mediate AMPA Receptor Endocytosis Induced by Oligomeric Amyloid-β. (5th July 2017) - Zhang, Jifeng; Yin, Yichen; Ji, Zhisheng; Cai, Zhenbin; Zhao, Bo; Li, Jiong; Tan, Minghui; Guo, Guoqing
Abstract : Amyloid- β (A β ) plays an important role in Alzheimer's disease (AD), as oligomeric A β induces loss of postsynaptic AMPA receptors (AMPARs) leading to cognitive deficits. The loss of postsynaptic AMPARs is mediated through the clathrin-dependent endocytosis pathway, in which endophilin2 is one of the important regulatory proteins. Endophilin2, which is enriched in both the pre- and postsynaptic membrane, has previously been reported to be important for recycling of synaptic vesicles at the presynaptic membrane. However, the role of endophilin2 in oligomeric A β -induced postsynaptic AMPAR endocytosis is not well understood. In this study, we show that endophilin2 does not affect constitutive AMPAR endocytosis. Endophilin2 knockdown, but not overexpression, resisted oligomeric A β -induced AMPAR dysfunction. Moreover, endophilin2 colocalized and interacted with GluA1, a subunit of AMPAR, to regulate oligomeric A β -induced AMPAR endocytosis. Thus, we have determined a role of endophilin2 in oligomeric A β -induced postsynaptic AMPAR dysfunction, indicating possible directions for preventing the loss of AMPARs in cognitive impairment and providing evidence for the clinical treatment of AD.